2022
DOI: 10.1038/s41467-022-30540-z
|View full text |Cite
|
Sign up to set email alerts
|

Breaking scaling relationships in alkynol semi-hydrogenation by manipulating interstitial atoms in Pd with d-electron gain

Abstract: Pd catalysts are widely used in alkynol semi-hydrogenation. However, due to the existence of scaling relationships of adsorption energies between the key adsorbed species, the increase in conversion is frequently accompanied by side reactions, thereby reducing the selectivity to alkenols. We report that the simultaneous increase in alkenol selectivity and alkynol conversion is achieved by manipulating interstitial atoms including B, P, C, S and N in Pd catalysts. A negative linear relationship is observed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 61 publications
6
47
0
Order By: Relevance
“…15). This demonstrated that Pd in Pd/Nb 2 C possess more populated 3d state electrons 30,49 , which is in accordance with the XPS results (Supplementary Fig. 16).…”
Section: Resultssupporting
confidence: 89%
“…15). This demonstrated that Pd in Pd/Nb 2 C possess more populated 3d state electrons 30,49 , which is in accordance with the XPS results (Supplementary Fig. 16).…”
Section: Resultssupporting
confidence: 89%
“…As listed in Table S3, the E D values of the H, N, and S atoms are 36.4, 86.5, and 129.9 kJ mol –1 , respectively. Thus, although the H, N, and S atoms are strongly adsorbed at the Pd(111) surface site, they can also exist at the Pd(111) subsurface site, which is also confirmed by the previously reported findings; for example, H can exist at the Pd subsurface as the Pd-hydride. , A recent study reported the successful synthesis of Pd nanocatalysts with interstitial N and S atoms …”
Section: Resultssupporting
confidence: 84%
“…The differential charge density also proves that only B or P heteroatoms lose an electron to the metal Pd, which is consistent with the electronegativity order of N (3.04) > S (2.58) > C (2.55) > H (2.20) > P (2.19) > B (2.04). Compared to the Pd catalyst, as the coverage of the same heteroatom increases, more charges are transferred between the heteroatom and surface Pd atoms, which plays a key role in regulating catalytic performance; , for example, as the d -charge of subsurface heteroatom-doped Pd increases, the adsorption configuration of CC functional groups changes and the adsorption ability on the catalyst becomes weaker, which was beneficial to the improvement of olefin selectivity, and the TOF value of 2-methyl-3-butyn-2-ol (MBY) hydrogenation increases linearly . Further, previous studies showed that the d-band center far from the Fermi level could improve CH x hydrogenation activity over metal catalysts .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the transition metal is modified by the heteroatom, the electronic structure of the metal surface will change, especially the d charge, and then, the adsorption configuration and adsorption energy of key species will be greatly changed. For example, Yang et al experimentally and theoretically explored the relationship between the d-band electron structure of Pd and the catalytic performance of alkynol semihydrogenation by introducing different types of heteroatoms, including B, P, C, S, and N, into the subsurface of Pd(111) and found that with the number of electrons occupying the d -level increasing, the bond strength between the CC bond and Pd is enhanced and the TOF value of 2-methyl-3-butyn-2-ol (MBY) hydrogenation increases linearly. On the contrary, the adsorption energy of 2-methyl-3-buten-2-ol (MBE) is weakened with the increase in the d charge, and the adsorption configuration is changed from the di-σ adsorption model of the CC bond to the vertical adsorption model of the O–H bond, which is conducive to the desorption of MBE, and the TOF value of MBE hydrogenation is significantly reduced, so the selectivity of MBE is greatly improved.…”
Section: Resultsmentioning
confidence: 99%